Resistance Against Cassava Brown Streak Viruses From Africa in Cassava Germplasm From South America - Sheat, Samar; Fuerholzner, Bettina; Stein, Beate; Winter, Stephan (Frontiers in Plant Science, 2019)
Cassava brown streak disease (CBSD) is a severe virus disease of cassava and prevalent in eastern regions of Africa. The disease is characterized by distinct vein chlorosis and streak symptoms on leaves and stems and necrosis of storage roots. This necrosis can encompass large areas of the root and rendering it inedible so that the entire cassava harvest can be lost. African cassava varieties are susceptible to either of the two viruses causing the disease, Cassava brown streak virus (CBSV) and Uganda cassava brown streak virus (UCBSV), and while there are less sensitive varieties, all cassava eventually succumb to the disease. The lack of CBSD resistance in African cassava varieties prompted this search for new sources of virus resistance in the diversity of South American cassava germplasm held in the collection at CIAT, Columbia. Our search for CBSD resistance in South American cassava germplasm accessions revealed that most of the 238 South American cassava lines infected with CBSV established systemic virus infections with moderate to severe disease symptoms on leaves and stems. Fifteen cassava accessions did not become virus infected, remained free of symptoms and CBSV was undetected by qRT-PCR. When tuberous roots of those lines were examined, necrotic tissue was found in eight lines and CBSV was detected. The remaining seven cassava accessions remained clear of symptoms on all tissues and organs and were virus-free. A broad spectrum of virus resistance also including other virus isolates was confirmed for the breeding lines DSC 167 and DSC 188. While detailed infection experiments with other cassava lines selected for resistance are still ongoing, this indicates that the resistance identified may also hold against a broader diversity of cassava brown streak viruses. Taken together, we present the results of a comprehensive study on CBSV resistance and susceptibility in cassava germplasm accessions from South America. The virus resistance in cassava germplasm identified provides compelling evidence for the invaluable contribution of germplasm collections to supply the genetic resources for the improvement of our crops.